Uji Efektivitas Antibakteri Ekstrak Kulit Batang Faloak (Sterculia quadrifida R.br) yang Tumbuh di Desa Bolok Terhadap Pertumbuhan Bakteri Salmonella Typhi - Aburizal Malik; Hawin Nurdiana; Indra Setiawan (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2023)
An impropriate use of antibiotics leads to bacterial resistance problems and side effects. To minimize resistance and adverse side effects, the faloak plant (Sterculia quadrifida R.Br.) has the potential to be used as antibacterial agents. This study aimed to determine the antibacterial effectiveness of faloak bark extract (Sterculia qudrifida R.Br.) against the growth of Salmonella typhi bacteria. This study used a static group comparison research method (Static Group Comparison), namely by measurement (observation) carried out after the treatment group received a program or intervention. According to the results of the research and discussion in this study, the following conclusions can be drawn. Extract of the bark of the faloak plant (Sterculia quadrifida R.Br.) with a concentration of 22.5%; 45%; 75%; and 100% has antibacterial effectiveness against the growth of Salmonella typhi bacteria. The stem bark extract of the faloak plant (Sterculia quadrifida R.Br.) is said to be most effective at inhibiting the growth of Salmonella typhi at a concentration of 100%.